2020
DOI: 10.3390/toxins12080492
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Botulinum Toxin Injections on Spasticity and Motor Performance in Chronic Stroke with Spastic Hemiplegia

Abstract: Spastic muscles are weak muscles. It is known that muscle weakness is linked to poor motor performance. Botulinum neurotoxin (BoNT) injections are considered as the first-line treatment for focal spasticity. The purpose of this study was to quantitatively investigate the effects of BoNT injections on force control of spastic biceps brachii muscles in stroke survivors. Ten stroke survivors with spastic hemiplegia (51.7 ± 11.5 yrs; 5 men) who received 100 units of incobotulinumtoxinA or onabotulinumtoxinA to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 54 publications
2
24
0
Order By: Relevance
“…47,48 It is also difficult for them to maintain a constant force output on the spastic-paretic side as compared with the contralateral side. 41,[49][50][51] The weaker the spastic muscle, the greater the force variability that was observed. 41 Spastic muscles are weak muscles.…”
Section: Abnormal Force Controlmentioning
confidence: 99%
“…47,48 It is also difficult for them to maintain a constant force output on the spastic-paretic side as compared with the contralateral side. 41,[49][50][51] The weaker the spastic muscle, the greater the force variability that was observed. 41 Spastic muscles are weak muscles.…”
Section: Abnormal Force Controlmentioning
confidence: 99%
“…The spasticity-related spontaneous motor neuron firing is not under voluntary control, and could be viewed as "motor noise" during voluntary activation. As such, they may make it difficult for stroke survivors to perform voluntary actions with spastic muscles, such as to initiate or terminate a hand grip [13,14] or maintain a constant force output [12,[15][16][17]. In other words, spasticity interferes with motor performance of spastic muscles [9].…”
Section: Introductionmentioning
confidence: 99%
“…This differentiation is important because BoNT injections also induce muscular changes and alter muscle stiffness [30]. It was found that both the MAS score and reflex torque of elbow flexor muscles significantly decreased 3 wks after BoNT injections, the non-reflex torque remained unchanged [17]. In a longitudinal study, the reflex torque of wrist flexors of stroke survivors decreased at 4 wks after BoNT injections, and returned to baseline levels at 12 wks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, how IZ is distributed is an essential component for understanding muscle morphology and its alterations in diseased states [1][2][3][4][5]. In clinical practice, identification of muscle IZ can help facilitate botulinum toxin injection for spasticity treatment [6][7][8][9]. Knowledge of muscle IZ is also helpful for episiotomy during child delivery to minimize the risk of sphincter denervation [10].…”
Section: Introductionmentioning
confidence: 99%